2018
DOI: 10.1155/2018/8963234
|View full text |Cite
|
Sign up to set email alerts
|

Mining Connected Vehicle Data for Beneficial Patterns in Dubai Taxi Operations

Abstract: On-demand shared mobility services such as Uber and microtransit are steadily penetrating the worldwide market for traditional dispatched taxi services. Hence, taxi companies are seeking ways to compete. This study mined large-scale mobility data from connected taxis to discover beneficial patterns that may inform strategies to improve dispatch taxi business. It is not practical to manually clean and filter large-scale mobility data that contains GPS information. Therefore, this research contributes and demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Unlike taxis, online car-hailing services can only carry passengers through network appointments and are not allowed to cruise (Service types of them are showed in Figure 1). Although both online car-hailing services and taxis can provide personalized and door-to-door services (both of them are on-demand mobility services, and taxis additionally can be used for street hailing [1]), some researchers have shown that there are certain differences in the travel characteristics between them. Cui et al [2] analyzed the online order data of taxis and express services (one type of online car-hailing service; the service and the price are roughly equal to a taxi) and found that, in terms of the travel time of taxi online orders, trips of less than 20 minutes account for 22.8% of all rides, trips of 20-30 minutes account for 24.5%, and trips of 30-40 minutes account for 21.2%.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike taxis, online car-hailing services can only carry passengers through network appointments and are not allowed to cruise (Service types of them are showed in Figure 1). Although both online car-hailing services and taxis can provide personalized and door-to-door services (both of them are on-demand mobility services, and taxis additionally can be used for street hailing [1]), some researchers have shown that there are certain differences in the travel characteristics between them. Cui et al [2] analyzed the online order data of taxis and express services (one type of online car-hailing service; the service and the price are roughly equal to a taxi) and found that, in terms of the travel time of taxi online orders, trips of less than 20 minutes account for 22.8% of all rides, trips of 20-30 minutes account for 24.5%, and trips of 30-40 minutes account for 21.2%.…”
Section: Introductionmentioning
confidence: 99%
“…Wali et al ( 26 ) presented data integration and the process steps in a data flow chart. Bridgelall et al ( 38 ) demonstrated an automated method of cleaning the data of a taxi probe dataset that utilized known distributions of vehicle operations to detect possible outliers for removal. Table 5 summarizes the shortcomings of the data and provides recommendations for data cleaning based on knowledge synthesized from the literature search.…”
Section: Resultsmentioning
confidence: 99%
“…Under the assumption that the central part of the TTD follows a well‐known distribution, Bridgelall et al. [30] proposed an outlier‐identification approach to remove outliers that moved the distributions further away from the known theoretical distributions, and chi‐squared statistical tests were used to validate the quality of the results. Park and Kim [31] proposed a similar approach of filtering the outliers repetitively in the travel time data, resulting in the remaining data resembling the normal distribution.…”
Section: Related Workmentioning
confidence: 99%